Calidad académica y satisfacción de los estudiantes de enfermería de la Universidad Nacional de Trujillo – Filial Valle Jequetepeque - Cabanillas Sánchez, Aldis Manuel (2023)
The present research, with a quantitative approach and descriptive-correlational level, carried out in the Valle Jequetepeque, had the general objective of determining the relationship between academic quality and satisfaction of nursing students at the National University of Trujillo - Valle Jequetepeque Branch. The study sample consisted of 86 students, distributed as follows: 24 from the III cycle, 24 from the V cycle, 22 from the VII cycle and 16 from the IX cycle. For data collection, 2 questionnaires were applied, a scale for the evaluation of academic quality and another scale to measure student satisfaction, both with Likert-type responses. Among the main results, it was found that there is a significant relationship between the study variables (p=0.00 < 0.05), likewise, the degree of correlation was high positive (Rho=0.807**). In relation to the levels of the dimensions of the academic quality variable, it was found that they are at a medium level. Similarly, the dimensions of the academic satisfaction variable, students rated with the lowest percentages at a high level. Finally, it was concluded that, if a better academic quality is provided in the nursing career, there will be greater satisfaction on the part of the students